2021
DOI: 10.1186/s12906-020-03169-y
|View full text |Cite
|
Sign up to set email alerts
|

In the presence of TGF-β1, Asperosaponin VI promotes human mesenchymal stem cell differentiation into nucleus pulposus like- cells

Abstract: Background The regeneration of nucleus pulposus (NP) cells is an effective method to prevent intervertebral disc degeneration (IVDD). In this study, we investigated the role of Asperosaponin VI (ASA VI), isolated from a traditional Chinese medicine (TCM), the root of Dipsacus asper Wall, in promoting human mesenchymal stem cell (HMSC) proliferation and differentiation into NP-like cells and explored the possible mechanism of action. Methods The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The ERK1/2 and Smad2/3 signaling pathways regulate the differentiation of NPMSCs into NP-like cells [74], and ASA VI modulates these pathways [142]. Hence, ASA VI was assessed for its effects on human MSCs, and it was confirmed that MSCs differentiate into NP-like cells [141].…”
Section: Molecules-exogenous Factorsmentioning
confidence: 93%
See 1 more Smart Citation
“…The ERK1/2 and Smad2/3 signaling pathways regulate the differentiation of NPMSCs into NP-like cells [74], and ASA VI modulates these pathways [142]. Hence, ASA VI was assessed for its effects on human MSCs, and it was confirmed that MSCs differentiate into NP-like cells [141].…”
Section: Molecules-exogenous Factorsmentioning
confidence: 93%
“…Asperosaponin VI (ASA VI) is an herbal Chinese traditional medicine with a long history of safe use in strengthening tendons and bones [141]. The ERK1/2 and Smad2/3 signaling pathways regulate the differentiation of NPMSCs into NP-like cells [74], and ASA VI modulates these pathways [142].…”
Section: Molecules-exogenous Factorsmentioning
confidence: 99%
“…Antibodies suitable for such proteins are usually used for fluorescence imaging [ 99 ]. Table 1 summarizes the studies that have monitored the differentiation process of stem cells over the past three years using immunocytochemistry [ 95 , 98 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 ]. ICC is a non-destructive method, different from Western blot.…”
Section: Latest Technological Advances In Monitoring Stem Cell Status...mentioning
confidence: 99%
“…Researchers have found that akebia saponin D (ASD), a triterpenoid saponin extracted from Dipsacus asper Wall, a traditional Chinese medicine, induces the proliferation and differentiation of various types of stem cells as well as angiogenesis under inflammatory conditions ( Ding et al, 2019 ; Gu et al, 2020 ; Niu et al, 2021 ; Chen et al, 2022 ). Several studies have shown that ASD can cross the blood-brain barrier to improve AD pathology and Aβ-induced cognitive deficits, as well as inflammation-induced depression ( Yu et al, 2012 ; Wang et al, 2018 ; Zhang et al, 2020c ; Stepnik, 2021 ).…”
Section: Introductionmentioning
confidence: 99%